P107 Embryonal rhabdomyosarcoma of uterus in adult women: a systematic review and survival analysis of 116 patients. (1st November 2019) - Pop, F-C; Stanciu Pop, C; Moreau, M; Jungels, C; Chintinne, M; Artigas, GC; Larsimont, D; Veys, I
Abstract : Introduction/Background: Uterine embryonal rhabdomyosarcoma (uERMS) in adult women is a malignant entityof mesenchymal origin that very rarely occurs in adult age. Almost all information's about uERMS is coming by case reports, and probably remains an under-recognized neoplasm. The treatment is not codified, and recommended strategies are mostly based on treatments for RMS of paediatric population. Methodology: A comprehensive database searches were performed for studies ofadult uERMS (>19 years). Survival probabilities were estimated using Kaplan-Meier Method and potential risk factors for survival were tested using the the Cox model. Results: 116 patients from 58 articles were included.Mean ages at diagnosis was 36.6 years. Forty-ninewomen were older than 40 years. In half of them, the most common presenting symptoms was vaginal bleeding only. The median tumor size was 5 cm(ranged 0.5–27 cm). Nearly 90% of patients were classified in the IRS Group-I. Surgery was the main therapeutic modality. With a median follow-up time of 24 months, the estimate overall survival (OS) and progression free survival (PFS) at 5 years was 81.4% and respectively 80.6%. In univariate analysis, age >36.6 years, deeply invasive tumors, and IRS Group >IA were associated with worst OS. In bivariate analysis the age higher than 36.6 years and IRSG >IA remained associated with death from uERMS. A trend towards for recurrence was seen in patients with age >36.6 years, deeply invasive tumors, and IRS Group >IA. Conclusion: Uterine ERMS is a very rare disease among adult women. Multidisciplinary approach is essential taking into account that therapeutic management is still controversial. A relatively good 5-years OS and PFS is possible with a combination of surgery, radiotherapy, and multiagent chemotherapy, but a significantly risk of death exist in women with advanced age, with deep tumor invasion, and with IRS Group >IA. Disclosure: Nothing to disclose.